PENGARUH PERPUTARAN PERSEDIAAN DAN PERPUTARAN HUTANG TERHADAP SOLVABILITAS. - Dyah Ayu Retno Inten, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
This research was conducted in manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2018 period. The research instrument this time is secondary data in the form of annual financial statements from the company. The population of this research is all manufacturing companies listing on the Indonesia Stock Exchange in 2016-2018, with a total population of 158 companies. Samples taken as many as 89 companies using purposive sampling. The results obtained from this study are inventory turnover variables have an influence on solvency. The variable Payable turnover has a negative effect on solvability.